Endovascular treatment of proximal lower extremity deep vein thrombosis – experience of a center - Queirós, Miguel (2024)
INTRODUCTION: Proximal lower extremity deep vein thrombosis (DVT) occurs in 5-10/10000 patients annually. Left untreated, there's a notable risk of pulmonary embolism development and the onset of long-term limb complications linked to post-thrombotic syndrome (PTS). Traditionally, these patients were treated with conservative therapy, namely anticoagulation and compression stockings. Nowadays, new and more aggressive treatments have emerged. Endovascular therapies, such as thrombectomy devices, catheter-directed thrombolysis (CDT), percutaneous transluminal angioplasty (PTA), and stent placement, provide a highly effective treatment option with minimal patient risk of complications. METHODS: We retrospectively studied all patients with proximal lower extremity DVT who were treated with endovascular therapy in our center between the years of 2018 and 2021. We choose as primary outcomes symptoms of PTS (Villalta Score) and quality of life (VEINES-QoL/Sym questionnaire) and as secondary outcomes treatment efficacy (grade of thrombolysis), treatment safety, and primary patency. RESULTS: A total of 20 patients were treated by endovascular treatment. The majority of these patients were women (95%); 60% of them had DVT of the left limb, and 30% had phlegmasia alba dolens. Seven patients were treated with the AngiojetTM system (35%), four with the PenumbraTM system (20%) and nine with CDT alone (45%). Two patients presented with mild PTS symptoms, and the mean VEINES-QoL/Sym questionnaire score was 84.8% +/- 13.6%. There were no cases of major bleeding or pulmonary embolism after the procedure. Two patients had small vein ruptures with no need for additional treatment. The average length of stay in a high surveillance unit for vigilance was 2.2 days. At the end of treatment, 75% of the patients had complete thrombolysis, 15% had partial thrombolysis (50–99% thrombus removal), and 10% showed minimal or no thrombolysis (< 50% thrombus removal). The primary patency rate was 88% after 12 months. CONCLUSION: Our experience has shown that endovascular therapy for acute proximal lower extremity DVT is a safe and effective treatment associated with a very low incidence of PTS and recurrent venous thromboembolism. However, life-threatening complications such as major bleeding can occur. As such, while under treatment, close monitoring of these patients in a high surveillance unit is mandatory.